Esther Greenwood's Distaste of Life as Seen in Sylvia Plath's The Bell Jar (NOBEL: Journal of Literature and Language Teaching, 2017)
This study attempts to analyze the causes and the effect of Esther Greenwood's distasteful feelings. The aims of this study are to understand what makes Esther has distaste of life including toward men, her friends, her mother and the general social's perspectives. It also explains the effect of Esther's distaste. This study uses descriptive qualitative method. Things that will be done are describing the causes and effect of Esther's distaste using Sigmund Freud's psychoanalysis. After analyzing the data, the result shows that Esther Greenwood has distaste for her life because of her unconscious mind. She got a lot of influences from her bad experiences including the time she spent with her ex-boyfriend, her mother, her friends, and also her opposite views toward the social perspectives. Then, the effect of Esther's distaste is that she tends to use defense mechanisms such as denial, fantasy, reaction formation, rationalization, repression, displacements, sublimation, undoing, and acting out, every time her distasteful feelings show up